2013
DOI: 10.1016/j.polymertesting.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the interlaminar behaviour of a carbon fabric reinforced thermoplastic lap shear specimen under quasi-static and tension-tension fatigue loading

Abstract: Although fusion bonded joints have already been extensively studied, they are only rarely compared to benchmark specimens with the same interlaminar behaviour of the composite material being joined, especially for the lapshear geometry. Even more, an extensive study of these benchmarks under quasi-static and fatigue loading conditions as almost never considered. In this manuscript, a method of producing such benchmark lapshear specimens is presented for a hot pressed carbon fabric reinforced thermoplastic. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…These authors moved further to examine the inter‐laminar behavior of a carbon fabric reinforced PPS by using lap experiments and they considered several loading conditions. The results showed that no crack growth was observed , both under quasi‐static loading until failure and successive loading‐unloading stages with increasing maximum load. Kytýr et al also evaluated impact damage effect on residual fatigue life of PPS composites reinforced by carbon fibers.…”
Section: Introductionmentioning
confidence: 96%
“…These authors moved further to examine the inter‐laminar behavior of a carbon fabric reinforced PPS by using lap experiments and they considered several loading conditions. The results showed that no crack growth was observed , both under quasi‐static loading until failure and successive loading‐unloading stages with increasing maximum load. Kytýr et al also evaluated impact damage effect on residual fatigue life of PPS composites reinforced by carbon fibers.…”
Section: Introductionmentioning
confidence: 96%
“…They found the constructed S–N curves shifted their trends dramatically at the maximum cyclic stress. In addition, Baere et al . examined the interlaminar behavior of a 5‐harness carbon fabric reinforced PPS by using lap experiments, they considered the quasi‐static, hysteresis, and fatigue loading conditions and they found that under quasi‐static loading, both until failure and with continuously loading and unloading with an increasing maximum load, there was no crack growth.…”
Section: Pps—high‐performance Polymer/properties Of Ppsmentioning
confidence: 99%
“…The GK algorithm is thus applied to estimate the parameters of a given set of k clusters on AE originated from QS tests. To cope with possibly additional AE sources that can occur during fatigue [28], an additional k + 1 th cluster is estimated based on fatigue data to include all feature vectors located "far" from the previous k clusters. For that, the boundary of each cluster characterized on QS tests is estimated by the average of the Mahalanobis-like distance (used in GK) [24].…”
Section: Ae Source Clusteringmentioning
confidence: 99%